SITUACION DE ABUSO SEXUAL BASADO EN IMAGENES EN MEXICO ENTRE 2017 Y 2018 (IMAGED-BASED SEXUAL ABUSE IN MEXICO BETWEEN 2017 AND 2018) - Ahuitz Rojas Sánchez (Universos Jurídicos, 2022)
Resumen: El objetivo de la presente investigación es explorar la estructura y el contenido de una red de usuarios de abuso sexual basado en imágenes en Twitter. Para ello se analizaron los perfiles de Twitter que contienen la palabra "Quemón o “Nudes” utilizando análisis de redes, técnicas de procesamiento natural del lenguaje. Entre 2017 y 2018 hubo una comunidad de abuso sexual basado en imágenes en Twitter. Al menos 329 usuarios se dedicaron y se auto describieron como cuentas sexualmente explícitas, vengativas, y en donde contenido sexual no consensual podía ser compartido de forma anónima. Ya con seguidores, la red comprende a más de 130,000 personas. Esta es una estimación conservadora, más cuentas podrían utilizar diferentes palabras clave, no tener ninguna descripción, o formar parte de comunidades privadas. Estos resultados sugieren que los consumidores de contenido de abuso sexual basado en imágenes son los principales responsables de su propagación. Abstract: This study aimed to explore the structure and content of an image-based sexual abuse user network on Twitter. For this purpose, Twitter profiles containing the word “Quemones” or "Nudes" were analyzed using network analysis, natural language processing techniques. Between 2017 and 2018 there was a community of image-based sexual abuse on Twitter. At least 329 users engaged in and self- described themselves as sexually explicit, vindictive accounts, and where nonconsensual sexual content could be shared anonymously. Already with followers, the network comprises more than 130,000 people. This is a conservative estimate; more accounts could use different keywords, have no description, or be part of private communities. These results suggest that consumers of image-based sexual abuse content are primarily responsible for its spread. Fuentes de Consulta: Allen, W. D. (2007). The Reporting and Underreporting of Rape. Southern Economic Journal, 73(3), 623–641. https://doi.org/10.2307/20111915 Angelides, S. (2013). ‘Technology, hormones, and stupidity’: The affective politics of teenage sexting. Sexualities, 16(5–6), 665–689. https://doi.org/10.1177/1363460713487289 Baum, M. A., Cohen, D. K., & Yuri, M. C. (2018). Rape Culture and Its Effects: Evidence from U.S. Newspapers, 2000-2013. Quarterly Journal of Political Science, 13(3), 263–289. Blondel, V. D., Guillaume, J.-L., Lambiotte, R., & Lefebvre, E. (2008). Fast unfolding of communities in large networks. Journal of Statistical Mechanics: Theory and Experiment, 2008(10), P10008. https://doi.org/10.1088/1742-5468/2008/10/P10008 Boeringer, S. B. (1994). Pornography and sexual aggression: Associations of violent and nonviolent depictions with rape and rape proclivity. Deviant Behavior, 15(3), 289–304. https://doi.org/10.1080/01639625.1994.9967974 Chou, W. S., Hunt, Y. M., Beckjord, E. B., Moser, R. P., & Hesse, B. W. (2009). Social Media Use in the United States: Implications for Health Communication. Journal of Medical Internet Research, 11(4). https://doi.org/10.2196/jmir.1249 CIET Africa. (1998). Prevention of sexual violence. A social Audit of the role of the police in the jurisdiction of Johannesburg’s Southern Metropolitan Local Council. Johannesburg. Citron, D. K., & Franks, M. A. (2016). Criminalizing Revenge Porn, 38. Crofts, T., Lee, M., McGovern, A., & Milivojevic, S. (2015). Sexting and Young People. UK: Palgrave Macmillan. Dir, A. L., & Cyders, M. A. (2015). Risks, Risk Factors, and Outcomes Associated with Phone and Internet Sexting Among University Students in the United States. Archives of Sexual Behavior, 44(6), 1675–1684. https://doi.org/10.1007/s10508-014-0370-7 Döring, N. (2014). Consensual sexting among adolescents: Risk prevention through abstinence education or safer sexting? Cyberpsychology: Journal of Psychosocial Research on Cyberspace, 8(1). Retrieved from https://cyberpsychology.eu/article/view/4303 Duxbury, S. W., & Haynie, D. L. (2018). The Network Structure of Opioid Distribution on a Darknet Cryptomarket. Journal of Quantitative Criminology, 34(4), 921–941. https://doi.org/10.1007/s10940-017-9359-4 Faloutsos, M., Faloutsos, P., & Faloutsos, C. (1999). On Power-Law Relationships of the Internet Topology. In Proceedings of the Conference on Applications, Technologies, Architectures, and Protocols for Computer Communication (pp. 251–262). Figueredo, A. J., Gladden, P. R., Sisco, M. M., Patch, E. A., & Jones, D. N. (2015). The Unholy Trinity: The Dark Triad, Sexual Coercion, and Brunswik-Symmetry. Evolutionary Psychology, 13(2), 147470491501300220. https://doi.org/10.1177/147470491501300208 Gámez-Guadix, M., Almendros, C., Borrajo, E., & Calvete, E. (2015). Prevalence and Association of Sexting and Online Sexual Victimization Among Spanish Adults. Sexuality Research and Social Policy, 12(2), 145–154. https://doi.org/10.1007/s13178-015-0186-9 Harkness, E. L., Mullan, B., & Blaszczynski, A. (2015). Association Between Pornography Use and Sexual Risk Behaviors in Adult Consumers: A Systematic Review. Cyberpsychology, Behavior, and Social Networking, 18(2), 59–71. https://doi.org/10.1089/cyber.2014.0343 Hsieh, H.-F., & Shannon, S. E. (2005). Three Approaches to Qualitative Content Analysis. Qualitative Health Research, 15(9), 1277–1288. https://doi.org/10.1177/1049732305276687 INEGI. (2017). Encuesta Nacional de Victimización y Percepción Sobe Seguridad Pública (ENVIPE) 2017 (p. 18). Mexico: Instituto Nacional de Estadística y Geografía. Retrieved from http://www.beta.inegi.org.mx/proyectos/enchogares/regulares/envipe/2017/ INEGI. (2018). Banco de Información Económica (BIE) (Data Base). Mexico: Instituto Nacional de Estadística y Geografía. Retrieved from http://www.inegi.org.mx/Sistemas/BIE/Default.aspx?Topic=0&idserPadre=10100360#D10100360 Jewkes, R., & Abrahams, N. (2002). The epidemiology of rape and sexual coercion in South Africa: an overview. Social Science & Medicine, 55(7), 1231–1244. https://doi.org/10.1016/S0277-9536(01)00242-8 Jonason, P. K., Girgis, M., & Milne-Home, J. (2017). The Exploitive Mating Strategy of the Dark Triad Traits: Tests of Rape-Enabling Attitudes. Archives of Sexual Behavior, 46(3), 697–706. https://doi.org/10.1007/s10508-017-0937-1 Karaian, L. (2014). Policing ‘sexting’: Responsibilization, respectability and sexual subjectivity in child protection/crime prevention responses to teenagers’ digital sexual expression. Theoretical Criminology, 18(3), 282–299. https://doi.org/10.1177/1362480613504331 Kjellgren, C., Priebe, G., Svedin, C. G., & Långström, N. (2010). Sexually Coercive Behavior in Male Youth: Population Survey of General and Specific Risk Factors. Archives of Sexual Behavior, 39(5), 1161–1169. https://doi.org/10.1007/s10508-009-9572-9 Kleinberg, J. M. (1999). Hubs, authorities, and communities. ACM Computing Surveys, 31(4es), 5-es. https://doi.org/10.1145/345966.345982 Makin, D. A., & Morczek, A. L. (2015). The Dark Side Of Internet Searches: A Macro Level Assessment Of Rape Culture. https://doi.org/10.5281/zenodo.22057 Marganski, A., & Melander, L. (2015). Intimate Partner Violence Victimization in the Cyber and Real World: Examining the Extent of Cyber Aggression Experiences and Its Association With In-Person Dating Violence. Journal of Interpersonal Violence, 1–25. Newman, M. E. J. (2001). Clustering and preferential attachment in growing networks. Physical Review E, 64(2). https://doi.org/10.1103/PhysRevE.64.025102 Newman, Mark E. J. (2016). Networks: an introduction (Reprinted). Oxford: Oxford University Press. Ojanen, T. T., Boonmongkon, P., Samakkeekarom, R., Samoh, N., Cholratana, M., & Guadamuz, T. E. (2015). Connections between online harassment and offline violence among youth in Central Thailand. Child Abuse & Neglect, 44, 159–169. https://doi.org/10.1016/j.chiabu.2015.04.001 Park, B., Wilson, G., Berger, J., Christman, M., Reina, B., Bishop, F., … Doan, A. (2016). Is Internet Pornography Causing Sexual Dysfunctions? A Review with Clinical Reports. Behavioral Sciences, 6(3), 17. https://doi.org/10.3390/bs6030017 Pina, A., Holland, J., & James, M. (2017). The Malevolent Side of Revenge Porn Proclivity: Dark Personality Traits and Sexist Ideology. International Journal of Technoethics, 8(1), 30–43. https://doi.org/10.4018/IJT.2017010103 Powell, A., & Henry, N. (2017). Sexual Violence in a Digital Age. Palgrave Macmillan. Powell, A., Henry, N., & Flynn, A. (2018). Image-Based Sexual Abuse. In Routledge Handbook of Critical Criminology (2nd Edition, pp. 305–315). Routledge. Priebe, G., & Svedin, C. G. (2012). Online or off-line victimisation and psychological well-being: a comparison of sexual-minority and heterosexual youth. European Child & Adolescent Psychiatry, 21(10), 569–582. https://doi.org/10.1007/s00787-012-0294-5 Reed, L. A., Tolman, R. M., & Ward, L. M. (2016). Snooping and Sexting: Digital Media as a Context for Dating Aggression and Abuse Among College Students. Violence Against Women, 22(13), 1556–1576. https://doi.org/10.1177/1077801216630143 SEGOB. (2018). Incidencia Delictiva del Fuero Común 2018 (pp. 1–68). Mexico: Secretaría de Gobernación; Secretariado Ejecutivo del Sistema Nacional de Seguridad Publica. Retrieved from http://secretariadoejecutivo.gob.mx/docs/pdfs/nueva-metodologia/CNSP-Delitos-2018.pdf Shearer, E., & Gottfried, J. (2017, September 7). News Use Across Social Media Platforms 2017. Retrieved February 22, 2018, from http://www.journalism.org/2017/09/07/news-use-across-social-media-platforms-2017/ Strohmaier, H., Murphy, M., & DeMatteo, D. (2014). Youth Sexting: Prevalence Rates, Driving Motivations, and the Deterrent Effect of Legal Consequences. Sexuality Research and Social Policy, 11(3), 245–255. https://doi.org/10.1007/s13178-014-0162-9 Thompson, M. P., & Morrison, D. J. (2013). Prospective predictors of technology-based sexual coercion by college males. Psychology of Violence, 3(3), 233–246. https://doi.org/10.1037/a0030904 Wagner, A. K., Soumerai, S. B., Zhang, F., & Ross-Degnan, D. (2002). Segmented regression analysis of interrupted time series studies in medication use research. Journal of Clinical Pharmacy and Therapeutics, 27(4), 299–309. https://doi.org/10.1046/j.1365-2710.2002.00430.x Walker, K., & Sleath, E. (2017). A systematic review of the current knowledge regarding revenge pornography and non-consensual sharing of sexually explicit media. Aggression and Violent Behavior, 36, 9–24. https://doi.org/10.1016/j.avb.2017.06.010 Walker, S., Sanci, L., & Temple-Smith, M. (2013). Sexting: Young Women’s and Men’s Views on Its Nature and Origins. Journal of Adolescent Health, 52(6), 697–701. https://doi.org/10.1016/j.jadohealth.2013.01.026